Innovative methods of an assessment of physical condition of a person as a factor of ensuring the effective management of a moving object - Valeriy Samsonkin; Yaroslavna Puhach; Valeriy Druz; Maria Cherednichenko; Vjаcheslav Shutieiev; Tetiana Shutieieva; Volodymyr Shishka; Victoria Gorinа (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to establish the basic provisions of influence of a human factor on reliability of functioning of the system "the person - the object of management - the activity environment". Materials and Methods: the general scientific methods of the analysis, analogy, deduction, comparison, statistical information processing. The methods of a statistical control of sample statistics on an alternative sign. The computer data processing with the use of Excel and Turbo Basic. Results: the method of an individual control and an assessment of influence of a human factor on safety of functioning of the system "the person - the object of management - the environment" is developed. Conclusions: the general provisions of the construction of the sign semantic spaces are established, which allow estimating the current functional state of a person-operator during his direct performance of the professional activity that provides control of its sufficient quality.